Impact of the people's republic of China's slowdown on the global economy - Soumyananda Dinda (Asian Development Bank Institute (ADBI), 2017)
Across the world, researchers and business analysts are closely watching the People's Republic of China (PRC), especially its recent economic slowdown. The Asia and Pacific region is extremely anxious about the PRC's slowdown, but the rest of the world has a definite reason to worry about the consequences of the slowdown in the world's second-largest economy. During the last few decades, the PRC has integrated strongly with Asia and also with the rest of the world. This paper investigates what the impact of the PRC's slowdown on the global economy is. If there is a crisis in the PRC, how much does it affect developed and emerging or developing economies? Using a panel data model, this paper focuses on these issues. The study considers international linking variables for the period 2000-2012. Evidence based on panel data analysis for six developed countries (G6: the United States, the United Kingdom, Germany, Japan, Canada, and Australia) and four BRICS countries (G4: Brazil, Russian Federation, India, and South Africa) shows that the impact of the PRC's slowdown is greater on emerging BRICS nations than on developed economies. The impact of the PRC's GDP growth shock on the rest of emerging Asia is greater since it has a strong production network in East and Southeast Asia. So, the PRC's slowdown certainly affects Asia more than Western developed economies.
Keywords: C32; O54; 330; the PRC's economic slowdown; global linking variable; GDP shock; emerging BRICS nations; developing country; developed economy; panel data